Towards bring your own device marketing policy. (11th September 2019) - Giotopoulos, Konstantinos C.; Halkiopoulos, Constantinos; Papadopoulos, Dimitris; Antonopoulou, Hera
Mobile technologies have brought the world of entrepreneurship in new challenges and perspectives by the establishment of a solid framework for the deployment of mobile hardware. The demand for mobile applications supporting the day-to-day office work provides the possibility to transfer work from PC to mobile terminals, realising the bring your own device (BYOD) policy. BYOD as one of important mobile office modes has received the academia's extensive attention in recent years. Contemporary methods deploy BYOD in several phases and stages like offline-online mobile office and intelligent mobile office. Towards this, BYOD has been introduced in sectors such as education, health, office mode, etc. The purpose of the specific paper is to introduce a BYOD policy concept in marketing based on high-end technological IT solutions. Through this research work a system framework will be defined aiming to combine technological trends with wireless marketing strategies integrating BYOD features.